Apoyo en la elaboración de presupuestos y supervisión de obras desarrolladas en la Secretaría de Planeación de la Alcaldía de Taminango Nariño (2021)
This document is presented for the development of the internship in the Secretariat of Planning, Infrastructure and Community Development of Taminango Nariño as a degree project, where the main support activities that will be carried out during the process will be: The update of prices for Lael design preparation of budgets for civil works, analysis of unit prices, and supervision or technical visits to works that are developed in the municipality during the period determined for the internship, through the use of different tools and photographic records; in order to provide the relevant technical support according to existing needs